PENGARUH CORPORATE ENVIRONMENTAL RESPONSIBILITY (CER) TERHADAP NILAI PERUSAHAAN DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIABEL MODERATING - Elysabeth Irma Lestari Wameyop, 11.42.02.0092; Hardiningsih, Pancawati (Jurnal Mahasiswa Pasca Sarjana, 2014)
The purpose of this study was to examine the influence of Corporate Environmental Responsibility (CER) to the value of the company with managerial ownership as a moderating variable. The population in this study were all manufacturing companies. listed on the Indonesia Stock Exchange from the period 2008 to 2011. The sample in this study is a manufacturing company in accordance with defined criteria. Regression analysis was performed on the basis of the results of the data analysis. This study concludes some of the following:. (1) Variable Corporate Environmental Responsibility (CER) proved to affect the value of the company, 2) proven managerial ownership variables affect the value of the company, (3) managerial ownership proved to act as moderating the relationship Corporate Environmental Responsibility (CER) with the value of the company. Keywords : Corporate Environmental Responsibility(CER), ManagerialÂ  Ownership and Firm Value